How Digital Food Affects Our Analog Lives: The Impact of Food Photography on Healthy Eating Behavior - Andersen, Tjark; Byrne, Derek Victor; Wang, Qian Janice (Frontiers in Psychology, 2021)
Obesity continues to be a global issue. In recent years, researchers have started to question the role of our novel yet ubiquitous use of digital media in the development of obesity. With the recent COVID-19 outbreak affecting almost all aspects of society, many people have moved their social eating activities into the digital space, making the question as relevant as ever. The bombardment of appetizing food images and photography – colloquially referred to as ‘food porn’ - has become a significant aspect of the digital food experience. This review presents an overview of whether and how the 1) viewing, 2) creating, and 3) online sharing of digital food photography can influence consumer eating behavior. Moreover, this review provides an outlook of future research opportunities, both to close the gaps in our scientific understanding of the physiological and psychological interaction between digital food photography and actual eating behavior, and, from a practical viewpoint, to optimize our digital food media habits to support an obesity-preventive lifestyle. We do not want to rest on the idea that food imagery's current prevalence is a core negative influence per se. Instead, we offer the view that active participation in food photography, in conjunction with a selective usage of food-related digital media, might contribute to healthy body weight management and enhanced meal pleasure.